2011
DOI: 10.4061/2011/798692
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptomatology in Children and Adolescents with Chronic Renal Insufficiency Undergoing Chronic Dialysis

Abstract: This paper presents a descriptive study, using the Birleson Scale to determine the frequency of depressive symptomatology in children and adolescents with chronic renal insufficiency (CRI) undergoing hemodialysis (HD) and chronic peritoneal dialysis (CPD). There were 67 patients (40 female and 27 male) with a mean age of 14.76 ± 2.71 years, duration of illness ≥3 months, 43 (64.18%) patients with CPD and 24 (35.82%) undergoing HD. The frequency of high occurrence, low occurrence, and absence of depressive symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
1
12
3
1
Order By: Relevance
“…A study done in Peru assessing depressive symptoms in children on dialysis did not find an association between depressive symptoms and demographic factors. 8 A study of pre-dialysis and dialysis pediatric CKD patients in Egypt also failed to find any associations with demographic or clinical factors. 10 Unfortunately, given their single center designs and small sample sizes, these findings may be reflective of inadequate power as opposed to a true lack of association and the possibility that there are other predictors of depression remains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study done in Peru assessing depressive symptoms in children on dialysis did not find an association between depressive symptoms and demographic factors. 8 A study of pre-dialysis and dialysis pediatric CKD patients in Egypt also failed to find any associations with demographic or clinical factors. 10 Unfortunately, given their single center designs and small sample sizes, these findings may be reflective of inadequate power as opposed to a true lack of association and the possibility that there are other predictors of depression remains.…”
Section: Discussionmentioning
confidence: 99%
“…This does not differ from the prevalence cited in the general adolescent population (7.5%) 7 and is substantially less than that identified in other pediatric CKD studies in which up to 35% of subjects were reported to suffer from depression. 6,812 One explanation for this unexpected finding may be that because CKiD is a large, rigorous, multicenter study requiring long term yearly follow-up, the children in this study come from a select group of patients with families that have the means to take the extra time to participate in the protracted time commitment of the study. Such a committed and organized family unit is likely protective against depression and may be the reason that depression was less prevalent in CKiD than in other smaller studies evaluating depression in CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently developed QoL questionnaires are easy to complete by patients and may act as a focus for early or longitudinal assessments [19,20]. There is increasing recognition of depression as being a major mortality risk in adult renal patients and depression may be more frequent than we have recognised in paediatric patients also [43].…”
Section: Preventing Psychosocial Issuesmentioning
confidence: 99%
“…Psychiatric disorders may develop as a response to being ill or in the hospital, to a threatening environment, as a result of genetic and psychosocial factors or may be secondary to metabolic disturbances related to the specific medical illness, or as a combination of all these factors [3,4,5,6] Psychiatric disorders can increase the severity of the preexisting physical illness by, among other ways, disturbing cardiac and nervous system, decreasing immune function or modulating nutritional conditions [7,8]. They can also influence patient compliance [9].…”
Section: Introductionmentioning
confidence: 99%